A neuropsychiatric systemic lupus erythematosus presenting with acute confusional state: a case report - Aliasghar Ebrahimi; Faegheh Ebrahimi Chaharom; Pouya Vakilipour; Sepideh Tahsini Tekantapeh (مجله پزشکی دانشگاه علوم پزشکی تبریز)
Systemic lupus erythematosus (SLE) is a chronic multisystem autoimmune disease characterized by variable clinical symptoms. It disproportionately affects African-American women and women from other ethnic groups. The complexity of SLE, stemming from its genetic and phenotypic diversity, poses challenges in diagnosis, treatment, and development of novel therapies. Neuropsychiatric systemic lupus erythematosus (NPSLE) encompasses a spectrum of neurological syndromes involving the central, peripheral, and autonomic nervous systems, as well as psychiatric syndromes diagnosed in SLE patients after ruling out other causes. Neuropsychiatric manifestations typically emerge in the later stages of SLE (10–75%). The acute onset of neuropsychiatric symptoms as the primary presentation of NPSLE is exceptionally rare and can be diagnostically elusive when other organs are unaffected. In this article, we present the case of a 53-year-old woman who was admitted to the hospital due to disorientation and an acute confusional state. Following the diagnosis of NPSLE, she received treatment consisting of three doses of pulse corticosteroids and one dose of cyclophosphamide. She exhibited a favorable clinical response, leading to partial resolution of her symptoms and subsequent discharge from the hospital. Practical Implications. Due to the rarity and diverse clinical presentations of NPSLE, particularly with the sudden onset of neuropsychiatric symptoms, there is a significant risk of delayed or incorrect diagnosis, which can lead to ineffective treatment. Therefore, maintaining a high index of clinical suspicion is paramount for achieving early and accurate diagnosis, which is crucial for initiating timely and effective treatment strategies.